2020
DOI: 10.21203/rs.3.rs-40529/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fear of COVID-19 and Mental Health: The Role of Mindfulness in During Time of Crisis

Abstract: Abstract The novel Coronavirus disease (COVID-19) is impactful on all aspects of individuals’ lives, particularly mental health due to the fear associated with the pandemic. Thus, current study explored the relationship between fear of COVID-19 and mental health aspects, namely anxiety and depression and whether this relationship is mediated by mindfulness. Data were collected from a student sample of 355 participants (71.5 % female and 28.5% males) ranged between in ag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Although it may cause people to experience less negative symptoms and anxiety during the COVID-19 outbreak, given the specific circumstances of cancer patients and many problems associated with the disease, the mindfulness may not affect the anxiety of cancer patients alone. The use of two different questionnaires, sampling at different times in different populations with different prevalence of COVID-19 may be the reasons for different results in the present study and the Belen’s study [ 56 ]. However, researchers have proposed mindfulness as a useful way to adapt to ongoing change and to cope with anxiety and depression during the coronavirus outbreak [ 57 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although it may cause people to experience less negative symptoms and anxiety during the COVID-19 outbreak, given the specific circumstances of cancer patients and many problems associated with the disease, the mindfulness may not affect the anxiety of cancer patients alone. The use of two different questionnaires, sampling at different times in different populations with different prevalence of COVID-19 may be the reasons for different results in the present study and the Belen’s study [ 56 ]. However, researchers have proposed mindfulness as a useful way to adapt to ongoing change and to cope with anxiety and depression during the coronavirus outbreak [ 57 ].…”
Section: Discussionmentioning
confidence: 95%
“…Numerous studies have shown that mindfulness is associated with reduced levels of anxiety and depression. [52][53][54][55] Belen 56 found that fear of COVID-19 and anxiety were inversely related to mindfulness and that more mindfulness might protect individuals against the negative effects of fear of coronavirus, anxiety and depression, and improve mental health during the COVID-19 epidemic. Mindfulness refers to the awareness and acceptance of the presence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on positive correlations between fear of one's own and relatives' threat appraisals and preventive behavior (Balkhi et al, 2020;Parlapani et al, 2020;Sahoo et al, 2020). In the context of the COVID-19 pandemic, an excessive fear at the individual level can often lead to mental problems (Belen, 2020;Fountoulakis et al, 2020). However, a lack of fear may prevent individuals from participating in preventive measures to reduce the spread of COVID-19 (Gerritsenb, 2020;Taheri-Kharameh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of another study also showed that there is a significant relationship between anxiety, mindfulness and psychological flexibility, both of which have been known to further decrease psychological distress (Dubey et al, 2020). Belen (2020) indicated that the fear of COVID-19 is reversely correlated with mindfulness while positive correlations were found with anxiety and depression and mindfulness mediated in the relationship between fear of COVID-19 and depression and anxiety.…”
mentioning
confidence: 91%